Actualization of Pancasila Values (Indonesian Ideology) in Majelis Taklim Organization - Rika Erliyana; Samsul Huda (Al-Hayat Al-Istiqomah Foundation, 2019)
This research begins based on observations of many cases of decadence in the actualisation of Pancasila values in various fields, especially in the field of education. Because of the lack of students' understanding of the importance of actualising Pancasila values in all aspects of life. This type of research is research and development (R & D). The results of this study: the more their awareness of the importance of divinity values, deepened their understanding of the significance of tasammuh attitude (morality), members of Majelis Taklim (Islamic study organization) prioritize public interests over personal and group interests, the existence of fair and free deliberation in determining activity plans, and their increased awareness of the importance of implementing simple life behaviors. The results of quantitative data analysis show that the products developed are feasible to be used as learning media in the activities of the Taklim Assembly Organization. This evidenced by the study of the overall data of the validator, and the score of 3.93 is in the